2014
DOI: 10.1080/10447318.2014.986639
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Structure and Player Experience in Role-Playing Games

Abstract: This article reports an experimental study that investigated the effects of narrative structure and number of salient decision points in a role-playing game (RPG). Previous research has proposed various theories and frameworks and posited that a branching structure with increased complexity (i.e., more salient decision points) will improve player's enjoyment. However, no empirical study has been conducted to validate these statements. This research attempts to fill in this gap. Two hypotheses were developed ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 17 publications
1
10
0
4
Order By: Relevance
“…The presence of a narrative suggests a story with “an identifiable beginning, middle, and end that provides information about scene, characters, and conflict; raises unanswered questions or unresolved conflict; and provides resolution” (Hinyard & Kreuter, 2007, p. 778). Narrative is particularly important for enjoyment of role-playing games, and it may be a strong predictor of transportation into such games (see Mahood & Hanus, 2015; Moser & Fang, 2015). However, we think transportation into a virtual gaming world can occur for reasons to do with the perceptual or interactive experience or with other gaming elements that have little to do with the narrative quality.…”
mentioning
confidence: 99%
“…The presence of a narrative suggests a story with “an identifiable beginning, middle, and end that provides information about scene, characters, and conflict; raises unanswered questions or unresolved conflict; and provides resolution” (Hinyard & Kreuter, 2007, p. 778). Narrative is particularly important for enjoyment of role-playing games, and it may be a strong predictor of transportation into such games (see Mahood & Hanus, 2015; Moser & Fang, 2015). However, we think transportation into a virtual gaming world can occur for reasons to do with the perceptual or interactive experience or with other gaming elements that have little to do with the narrative quality.…”
mentioning
confidence: 99%
“…Players can feel a stronger connection to their character through the use of role-playing and story narrative (Moser, & Fang, 2015). Additionally in role-playing games players tend to connect to how the character is played rather than how the character physically looks (Shaw, 2010).…”
Section: Character Backstorymentioning
confidence: 99%
“…Joyce (2015) states that when choices are offered in narrative-focused video games, players must be able to deliberate on their choices carefully and critically so their actions are the result of intent, and they must be able to understand their options and care about them. It also has been suggested that presenting the player with significant decisions makes them believe they have more choices than they might actually have (Moser & Fang, 2015)—a technique that the Mass Effect trilogy employs. An example is the suicide mission quest in Mass Effect 2 where the PC of Shepard must assign roles to various squadmates during the mission.…”
Section: Literature Reviewmentioning
confidence: 99%